PRAPERADILAN JULIET ASRIL SEBAGAI TERSANGKA PIDANA KORUPSI (PUTUSAN NOMOR 3/PID.PRA/2021/PN.TPG): Juliet Asril Pretrial as a Criminal Suspect of Corruption (Decision Number 3/Pid.Pra/2021/PN.Tpg) - Dinanti, Bernandia Hamsyah; Setiyono (AMICUS CURIAE, 2024)
Pretrial Request Number 3/Pid.Pra/2021/PN.Tpg from the Tanjung Pinang District Court, citing expiration as the basis for the request. This study focuses on how Pre-trial object arrangements are governed by the Criminal Procedure Code in relation to the Constitutional Court's decision No. 21/PUU-XII/2014 and whether the legal considerations and dictum of the Pretrial decision No. 3/Pid.Pra/2021/PN.Tpg were in accordance with the provisions of the Criminal Procedure Code and the Constitutional Court's decision No. 21/PUU-XII/2014. The author conducted normative research in order to respond to this query. Data management is conducted qualitatively, with reference to secondary data or library materials, while analysis and conclusion-drawing are qualitatively descriptive and deductive, respectively. Conclusions drawn from the research and discussion are that the legal considerations and the judge's dictum in Tanjungpinang District Pre-Trial Case Number 3/Pid.Pra/2021/PN.Tpg are not appropriate because there are only two grounds for determining a suspect: the allegation that the suspect committed a crime and the existence of sufficient preliminary evidence.